Peran Supervisi Akademik Kepala Sekolah dalam Meningkatkan Kinerja Guru tingkat Sekolah Dasar - Aini, Ilmi; Hariri, Hasan (9 772338317006, 2023)
Abstract: The Role of Principal Academic Supervision in Improving Teacher Performance at the Elementary School Level. The most fundamental problem in the education unit is how supervision efforts are made by the school principal to improve teacher performance, especially in elementary schools (SD). This becomes a task that cannot be abandoned by a school principal, because it is a form of responsibility of a leader in terms of improving teacher performance. By increasing teacher performance, school performance will also be better. The research method in this article uses the library research method (Library Research). This research method relates to library data collection methods. Data collection techniques in this study use documentation and data analysis techniques. or certain values that are believed by researchers related to the problem of supervising school heads through documents related to the problems that researchers examine. The results of this research are that academic supervision carried out by the principal can improve teacher performance at the school, because teachers receive supervision, the principal also provides feedback when there are teachers carrying out academic supervision, so that they continue to motivate teachers to improve their professionalism in teaching. Implementation of academic supervision by school principals is based on the need to overcome problems with learning tools, lesson plans, learning materials, class management, assessment of learning outcomes, teacher discipline, and implementation of character education. Several methods can be used and implemented by the principal as a supervisor in carrying out academic supervision activities to improve teacher performance, namely: guidance for teachers, education and training, and increasing teacher motivation.Keywords: Supervision, Principal, Teacher Performance